2021
DOI: 10.1051/shsconf/20219206038
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Behaviour of Generation Z in the Context of Dual Quality of Daily Consumption Products on EU market

Abstract: Research background: The paper focuses on the issue of dual quality of daily consumption products through the lens of the Z generation. Z generation is a generation of people born between years of 1997-2012, a generation that will become the main purchasing power in a few years. Purpose of the article: The purpose of the research was to explore the possibility whether the information on dual product quality affects the consumer behaviour of members of Z generation and if so, to what extent and at what type of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…33 On the other end of the scale is Generation Z's (born 1997-2012) prominence as consumers. 34 The demographic shifts, pose a central challenge in youth ministry as the coexistence of millennials (ages [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] and Generation Z within the church reflects an evolving landscape at the intersection of youth and faith.…”
Section: Impact On Youth Development: Challenges and Opportunitiesmentioning
confidence: 99%
“…33 On the other end of the scale is Generation Z's (born 1997-2012) prominence as consumers. 34 The demographic shifts, pose a central challenge in youth ministry as the coexistence of millennials (ages [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] and Generation Z within the church reflects an evolving landscape at the intersection of youth and faith.…”
Section: Impact On Youth Development: Challenges and Opportunitiesmentioning
confidence: 99%
“…They need to be successful and want to have quality things. They do not believe what companies try to tell them, or what retail chains offer them (Šramková & Sirotiaková, 2021). As Grabiwoda points out, Gen Z consumers are making more conscious and ethically responsible consumer Pobrane z czasopisma Annales H -Oeconomia http://oeconomia.annales.umcs.pl Data: 01/06/2024 19:05:14 choices.…”
Section: Consumer Trustmentioning
confidence: 99%
“…They understand that other nationalities have varied interests and preferences and that products made by global corporations must also accommodate these nationalities. One study found that Z-generation consumers, especially college-educated women and those residing in rural areas, were affected by news of the dual quality of goods available in the European Union market (Šramková & Sirotiaková, 2021). Using the theory of planned behavior (TPB) model, researchers discovered that market mavens, technology self-efficacy, and social identity best represent the distinct elements driving Generation Z's purchasing behavior.…”
Section: Literature Reviewmentioning
confidence: 99%